Articulating frets. About articulation as structuring element of the musical performance of the guitar (2019)
This article deals with music as a structuring element for the interpretation of the universal repertoire for solo guitar. For this proposal, we start from the conception of music as a language and the musical pieces for which the technique must be at your service. The objective is to structure the process of fingering for the interpretation of the pieces, both those that were conceived for the guitar and those that are adaptations of pieces written for other instruments.